Near infrared II laser controlled free radical releasing nanogenerator for synergistic nitric oxide and alkyl radical therapy of breast cancer. Issue 25 (17th June 2021) - Wu, Weiwei; Yang, Yan; Liang, Zhuoying; Song, Xiling; Huang, Yadong; Qiu, Lin; Qiu, Xiaozhong; Yu, Siming; Xue, Wei
Abstract : A multifunctional nanogenerator with NIR II-precise-control NO and alkyl radical release property is elaborately fabricated, which displays a synergistic NO and alkyl radical anticancer effect by significantly inhibiting breast tumor. Abstract : Recently, alkyl radicals have attracted much attention in cancer therapy due to their oxygen-independent generation property. For the first time, alkyl radical and nitric oxide (NO) combined therapy is demonstrated as an effective strategy for tumor inhibition. As a proof of concept, a biocompatible free radical nanogenerator with near-infrared (NIR) II laser-induced simultaneous NO and alkyl radical release property was elaborately fabricated. In particular, an NIR II molecule (IR 1061), NO donor (BNN6) and alkyl radical initiator (AIPH) were firstly encapsulated in a natural lecithin stabilized phase change material, and then further functionalized by an amphiphile of DSPE-PEG-RGD with specific tumor targeting ability, finally obtaining biocompatible P(IR/BNN6/AIPH)@Lip-RGD. Upon NIR II laser irradiation, the photothermal effect generated from IR 1061 could trigger the phase change of the nanogenerator by releasing the encapsulated BNN6 and AIPH, and subsequently decompose them to generate highly active NO and alkyl radicals. Remarkably, NO and alkyl radical release profiles of P(IR/BNN6/AIPH)@Lip-RGD could be precisely controlled using intermittent NIR II laser irradiation. Moreover, P(IR/BNN6/AIPH)@Lip-RGD displayed a synergistic NO and alkyl radicals' anticancer effect by significantly inhibiting the growth of breast tumors, upon NIR II laser exposure. Furthermore, an in depth mechanistic study revealed that synergistic NO and alkyl radical effect induced cancer cell apoptosis through a mitochondria-mediated apoptotic pathway. The synergistic effect jointly caused a burst generation of mitochondrial ROS, which significantly down-regulated Bcl-2 protein expression, accelerated cytochrome c release and triggered a cascade of apoptosis-related proteins of Caspase-3 and Caspase-9.